I am a newbie in Prolog, and I am trying to understand how a grammar can be translated into a normal definite clause from a DCG. I understood that DCG notation is just syntactic sugar for normal definite clauses in Prolog. I started to depict some similarities between the normal definite grammars, and the DCGs, but failed to apply the same pattern, so I am asking is there some rules that I am missing or an algorithm of conversion that might work.

Here is the grammar that I am working on, and here is what I did in order to translate that grammar:

```
expr --> term, addterm.
addterm --> [].
addterm --> [+], expr.
term --> factor, multfactor.
multfactor --> [].
multfactor --> [*], term.
factor --> [I], {integer(I)}.
factor --> ['('], expr, [')'].`
```

This grammar actually checks the syntactic correctness of arithmetic operations. The first rule is actually easy to convert as its pattern is similar to normal definite grammars, and so is the 4th one. However I have no clue about the other four. Here is How I converted the rule:

```
expr(E0,E) :- term(E0,E1), addterm(E1,E).
```